Effectiveness of a comic book intervention on mental health literacy among adolescents and youth in Burkina Faso: a randomized controlled trial protocol - Irene Brandt; Sylvain Some; Ourohiré Millogo; Oumar Sourabié; Jacob Burns; Sachin Shinde; Matthias Haucke; Nathan Sivewright; Christine Neumann; Shraddha Bajaria; Katian Napon; Clarisse Dah; et al. (BMC Public Health)
Abstract Background In Burkina Faso, nearly half of the population is under 15 years old, and one in four adolescents experience depression. This underscores the critical need to enhance mental health literacy among adolescents and youth, empowering them to manage their mental well-being effectively. Comic books offer an engaging approach to health education, yet their effectiveness in addressing mental health remains largely untested. Our study aims to fill this gap by evaluating the effectiveness of comic books in enhancing mental health literacy among adolescents and young adults aged 10–24 years. Methods We will recruit 2,007 participants aged 10–24, stratify them by age, and randomly assign them to three groups (1:1:1): a comic book intervention group (Intervention 1), a text-only flyer group (Intervention 2), and a control group with no intervention. The primary outcome will be mental health literacy and secondary outcomes will include anxiety, depression, and intentions to cope. Discussion We hypothesize that the comic book intervention and flyer intervention will prove more effective in improving mental health literacy than the control group. We further hypothesize that for younger adolescents (10–14), the comic book will be more effective at increasing mental health literacy than the flyer. Conversely, we hypothesize that the flyer will be more effective in increasing mental health literacy for older adolescents (15–24). Our study will provide evidence on novel interventions designed to enhance mental health literacy among adolescents and young adults in low-resource settings. Trial registration This trial has been registered on the German Clinical Trials Register (DRKS), with the registration number DRKS00034242.